Efficacy of pro‐ and anticoagulant strategies in plasma of patients undergoing hepatobiliary surgery. (10th September 2020) - Bos, Sarah; van den Boom, Bente; Ow, Tsai‐Wing; Prachalias, Andreas; Adelmeijer, Jelle; Phoolchund, Anju; Dunsire, Fraser; Milan, Zoka; Roest, Mark; Heaton, Nigel; Bernal, William; Lisman, Ton
Abstract: Background: In vitro efficacy of pro‐ and antihemostatic drugs is profoundly different in patients with compensated cirrhosis and in those who have cirrhosis and are critically ill. Objectives: Here we assessed the efficacy of pro‐ and anticoagulant drugs in plasma of patients undergoing hepato‐pancreato‐biliary (HPB) surgery, which is associated with unique hemostatic changes. Methods: We performed in vitro analyses on blood samples of 60 patients undergoing HPB surgery and liver transplantation: 20 orthotopic liver transplantations, 20 partial hepatectomies, and 20 pylorus‐preserving pancreaticoduodenectomies. We performed thrombin generation experiments before and after in vitro addition of fresh frozen plasma (FFP), prothrombin complex concentrate (PCC), recombinant factor VIIa (rFVIIa), low molecular weight heparin (LMWH), unfractionated heparin, dabigatran, and rivaroxaban. Results: We showed that patients undergoing HPB surgery are in a hypercoagulable state by thrombin generation testing. FFP and rFVIIa had minimal effects on thrombin generation, whereas PCC had a more pronounced procoagulant effect in patients compared with controls. Dabigatran showed a more pronounced anticoagulant effect in patients compared with controls, whereas rivaroxaban and LMWH had a decreased anticoagulant effect in patients. Conclusion: We demonstrate profoundly altered in vitro efficacy of commonly used anticoagulants, in patients undergoing HPB surgery compared with healthy controls, which may have implications for anticoagulant dosing in the early postoperative period. In the correction of perioperative bleeding complications, PCCs appear much more potent than FFP or rFVIIa, and PCCs may require conservative dosing and caution in use in patients undergoing HPB surgery.